INTERACTIVE APPROACH TO THE STUDENT'S MENTAL ACTIVITY THROUGH COLORS - Nuriddinova Mokhlaroyim (Scholar Express Journal, 2023)
This article talks about influencing students' cognitive skills through various interactive techniques and the practical introduction of techniques that can be applied to lesson processes from colors available in nature.
Keywords: educational system; mental activity; innovative approach